Metode Discovery dalam Pembelajaran Bahasa Arab Virtual - Khoirul Faizin; Frida Akmalia (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2021)
This study is in reliance on the anxiety of researchers in Arabic online education which they felt was not optimal and could not provide completed understanding to students. This attracted the attention of researchers to conduct a distant study of the learning methods, namely a discovery method. The researchers try to apply this method for online Arabic learning. This experiment was carried out on students of the special Arabic deepening program at STAI Attanwir, which consisted of 20 students. By using a quantitative model research and found the results of a significance value (P) of -2.0244> T-count <2.024 and because T-count (-35901) is not between -2.0244 and 2.024, in this case it means that H0 is rejected with other words H1 must be accepted. Therefore, the existence of the discovery method in online learning is stated to have a meaningful impact on the understanding of students in receiving Arabic language material presented virtually.